Resiliensi Anak Korban Perceraian dalam Perspektif Psikologi Pendidikan Islam: Studi Literatur - Anshori, Nanang; Rokhimah, Siti (TSAQOFAH, 2026)
Parental divorce can have psychological impacts on children, including emotional stress, anxiety, and difficulties in adjustment; however, some children are able to endure and develop positively through resilience. This study aimed to analyze the concept of resilience among children affected by parental divorce from the perspective of Islamic educational psychology through a literature study. The study employed a qualitative approach with a literature study design, drawing on relevant books and journal articles collected through documentation techniques and analyzed using Miles and Huberman’s interactive analysis model. The findings indicate that resilience in children affected by parental divorce is a dynamic adaptive capacity shaped by internal factors and environmental support, particularly from family and school. Education plays a strategic role in fostering resilience by providing supportive learning environments and strengthening socio-emotional skills. From the perspective of Islamic educational psychology, resilience is reinforced by spiritual values such as sabar, tawakkal, riḍā, and syukur, which help children interpret divorce as a life trial. Integrating psychological approaches with Islamic educational values forms a comprehensive framework for strengthening resilience among children affected by parental divorce and provides a conceptual basis for developing educational interventions oriented toward enhancing children’s psychological resilience.